环境讲章 - Rolston, Holmes, 1932-2025, author; Taiwan Ecological Stewardship Association, publisher (Colorado State University. Libraries, 2007)
Biblical faith originated with a land ethic. Within the covenant, keeping the commandments, the Hebrew people entered a promised land. Nature is the creative, generative powers on Earth. Spirit is the animating principle that raises up life from the ground. Christian citizens ought to join others shaping a public environmental ethic. Earth is promised planet, planet with promise, sacred, holy ground.
Preaching on the environment
Huan jing jiang zhang
Text in Chinese.
Translated by Chen, Tzu-Mei; original English version in Journal for Preachers 23 (2000).
Keywords: ecological covenant; land ethics; justice; integrity of creation; peace; ecosystems; environmental ethics; ecumenical covenant; Christianity; Judaism